Treatment Of Anaerobically Digested Palm Oil Mill Wastewater Using Sequencing Batch Reactor (Sbr) - Lim, Jing Xiang (2013)
In Malaysia, biological treatment which consist of series of anaerobic and aerobic ponds is being widely used to treat palm oil mill wastewater. Although there are many researches regarding the anaerobic system of the biological treatment but the studies of aerobic treatment is still scarce. An aerobic treatment is used to further reduce the chemical oxygen demand (COD) content of the anaerobically treated POM wastewater in order to meet the discharge requirement. In this study, sequencing batch reactor (SBR) was used to enrich biomass for the biological treatment of the aerobically treated POM wastewater. The SBR has a working volume of 8 L and an exchange ratio of 25%. The influent concentration of the POM wastewater was varied from 5000 ± 500 mg COD/L to 11500 ± 500 mg COD/L. The dissolved oxygen (DO) was controlled in the range of 4.0 to 5.5 mg/L, whereas the pH was not controlled. The performance of the reactor was monitored at different organic loading rates (OLR) and hydraulic retention time (HRT). It was found that around 90 % of the COD content of the POM wastewater has been successfully removed regardless of the OLR and HRT applied to the SBR. The remaining 10% of the COD in the effluent suggests that the POM wastewater contains around 10 % of non-biodegradable or slowly biodegradable COD which cannot be degraded by the biomass within the HRT of 5 days. It was found that the oxygen uptake near the end of each treatment cycle might due to oxidation of storage product by the biomass. Further, it is revealed that the increase of OLR increases the biomass concentration which results in the formation of small dispersed biomass with reduced settleability. Apart from that, the growth kinetic of the aerobic biomass was evaluated.